2018
DOI: 10.1007/s00704-018-2606-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of karst rocky desertification on regional climate in Southwest China with WRF

Abstract: It has been confirmed that the karst rocky desertification (KRD) has severely changed the interactions between atmosphere and terrestrial ecosystem which would cause a significant effect on regional climate system. In this study, the Weather and Research Forecasting model was applied to investigate the biogeophysical impact on temperature and precipitation change by land use/land cover change data with different KRD conditions in 1993KRD conditions in , 2003KRD conditions in , and 2013 in Southwest China. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Conversely, a decrease in KRD can improve the regional environment and benefit production and living conditions. For example, increasing the vegetation cover and thus lowering bedrock exposure decreases the local temperature, favoring crop growth and yield (Yang et al, 2019). In the environment restoration process, combating KRD and alleviating poverty are closely linked with the increase of ecological and economic benefits (Li & Xiong, 2021;Zhang et al, 2016).…”
mentioning
confidence: 99%
“…Conversely, a decrease in KRD can improve the regional environment and benefit production and living conditions. For example, increasing the vegetation cover and thus lowering bedrock exposure decreases the local temperature, favoring crop growth and yield (Yang et al, 2019). In the environment restoration process, combating KRD and alleviating poverty are closely linked with the increase of ecological and economic benefits (Li & Xiong, 2021;Zhang et al, 2016).…”
mentioning
confidence: 99%
“…Our present findings clarify that the use of an invariant reference state across the whole study area is questionable, particularly for studies conducted over a large geographic area (Liu et al, 2015; Zhang et al, 2017). Low NDVI values are easily identified as high KRD classes in several case studies (Yang et al, 2019; Zhang et al, 2017), however, not KRD but low temperatures in high elevations may limit the vegetation growth and result in the low NDVI. We suspect that this is why incidences of KRD mapping biases were found in previous studies in south‐western China when using a uniform reference.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of influence (D i ) and the degree of influence (C i ) of an element i were added to obtain the centrality of the element, denoted as M i . Centrality indicates the position of the factor in the evaluation index system and the size of its role, as shown in Equation (11).…”
Section: Index Weight Calculation Methodsmentioning
confidence: 99%
“…Under the background of the Chinese government's implementation of KRDC and ecological civilization construction, China's ecological environment and landscape pattern have undergone significant changes [8][9][10]. The serious KRD problem in karst areas of Southwest China has been gradually addressed, the degree of KRD has been reduced, and the impact of ecological damage has diminished [11][12][13]. The results of China KRD monitoring showed that the area of KRD in Guizhou Province decreased by 8457 km 2 in 2016 compared with 2005 [14].…”
Section: The Progress Karst Rocky Desertification Control In Chinamentioning
confidence: 99%